Предмет: Математика,
автор: heraman747
Даю 50 баллов! помогите!
Приложения:
Ответы
Автор ответа:
1
Пошаговое объяснение:
№1
а) (–1,2*(m^2)*(n^6))^2= (–1,2)^2*(m^2)^2*(n^6)^2 =1,44*(m^4)* (n^12)
б)(–0,2*(p^8)*(q^2))^3= (–0,2)^3*(p^8)^3*(q^2)^2 =–0,008*(p^24)*(q^6)
№2
a) (a^4)^3 * (a^8)^2= (a^12)*(a^16)=a^28
b) (a^6)^3 * (a^3)^5= (a^18)*(a^15)= a^33
в) (a^7)^6 * (a^3)^3= (a^42)*(a^9)=a^51
№3
7^12=(7^2)^6
7^12= (7^3)^4
7^12=(7^4)^3
с основанием 7^5 нельзя
7^12=(7^6)^2
с основанием 7^10 нельзя
№4
а) (х^6)^2 * х^m= (x^12)* (x^m)= x^(12+m)
б) (х^m)^3 * (x^3)^5= (x^3m)*(x^15)= x^(3m+15)
в) (х^5m)^4 * (x^(m+2))= (x^20m)*(x^(m+2))= x^(21m+2)
г) (х^(m+1)) * (x^3m)^3= (х^(m+1)) * (x^9m)= x^(10m+1)
Похожие вопросы
Предмет: Русский язык,
автор: ololololololololoaee
Предмет: Английский язык,
автор: Аноним
Предмет: Українська мова,
автор: zgeka
Предмет: Физика,
автор: minibaevadiano